(3GdefgL GdeSdhc aj SjGSI Gdedhcs - (3YHO GdaJGM Hf eUWajs ((3MLGRi Hf GdMGL eUWai GdGedjWi GdeGdci s)
(3ChdgG (B:s
(3bGd GHf YHO Gddg deG cGf Gdehcd GdfGUQ UdGM GdOjf CejQ GdeDefjf gPG GdcJGH hgh jMJhi Ydi WGQja ef GdMceI ef GdCOH hCUhd ef GdSjGSI s
(3BNQgG (B:s
(3heG CbUO CjGe hUdi cCfgG SGYGJ s
(3HgG WeS TOjOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs